Association Mapping of Drought Tolerance Indices in Ethiopian Durum Wheat (Triticum turgidum ssp. durum) - Negisho, Kefyalew; Shibru, Surafel; Matros, Andrea; Pillen, Klaus; Ordon, Frank; Wehner, Gwendolin (Frontiers in Plant Science, 2022)
Ethiopia is a major producer of durum wheat in sub-Saharan Africa. However, its production is prone to drought stress as it is fully dependent on rain, which is erratic and unpredictable. This study aimed to detect marker-trait associations (MTAs) and quantitative trait loci (QTL) related to indices. Six drought tolerance indices, i.e drought susceptibility index (DSI), geometric mean productivity (GMP), relative drought index (RDI), stress tolerance index (STI), tolerance index (TOL), and yield stability index (YSI) were calculated from Least-Squares Means (lsmeans) of grain yield (GY) and traits significantly (p < 0.001) correlated with grain yield (GY) under field drought stress (FDS) and field non-stress (FNS) conditions. GY, days to grain filling (DGF), Soil Plant Analysis Development (SPAD) chlorophyll meter, seeds per spike (SPS), harvest index (HI), and thousand kernel weight (TKW) were used to calculate DSI, GMP, RDI, STI, TOL, and YSI drought indices. Accessions, DW084, DW082, DZ004, C037, and DW092 were selected as the top five drought-tolerant based on DSI, RDI, TOL, and YSI combined ranking. Similarly, C010, DW033, DW080, DW124-2, and C011 were selected as stable accessions based on GMP and STI combined ranking. A total of 184 MTA were detected linked with drought indices at –log10p ≥ 4.0,79 of which were significant at a false discovery rate (FDR) of 5%. Based on linkage disequilibrium (LD, r² ≥ 0.2) six of the MTAs with positive effect on GY-GMP were detected on chromosomes 2B, 3B, 4A, 5B, and 6B, explaining 14.72%, 10.07%, 26.61%, 21.16%, 21.91%, and 22.21% of the phenotypic variance, respectively. The 184 MTAs were clustered into 102 QTLs. Chromosomes 1A, 2B, and 7A are QTL hotspots with 11 QTLs each. These chromosomes play a key role in drought tolerance and respective QTL may be exploited by marker assisted selection for improving drought stress tolerance in wheat.